Usefulness of white blood cell count to mean platelet volume ratio in predicting short term, 30 days major adverse cardiac events in patients presenting with acute coronary syndrome - Shanker, Sumit; Reddy, Subba; Ramachandran, Ganesan (International Journal of Research in Medical Sciences, 2020)
Background: The role of white blood cell (WBC) to mean platelet volume (MPV) ratio (WMR) in predicting short-term major adverse cardiac events (MACE) in patients presenting with acute coronary syndrome (ACS) has not been studied extensively. We aimed to determine whether WMR can predict short-term (30 days) MACE in ACS patients. Methods: This hospital-based prospective cohort study was undertaken at a tertiary-care teaching hospital in India from January 2018 to December 2018. Fifty patients presenting with ACS to undergo primary percutaneous intervention were evaluated for WMR and short-term MACE. Results: Receiver operating characteristic (ROC) curve showed cut-off value of WMR as 1059 with area under the ROC curve of 0.825 (SE=0.074; 95% CI: 0.679-0.971; p=0.001). MACE was noted in 10 patients (20%) and mortality in 4 patients (8%). WMR with cut-off value of 1059 was significant and highly accurate in predicting MACE (diagnostic accuracy: 72%, sensitivity: 80%, specificity: 70%, positive predictive value: 40%, negative predictive value: 93.33%, p=0.016, and positive likelihood ratio: 2.67, negative likelihood ratio: 0.29). Risk of short-term MACE increases with higher respiratory rate, creatine kinase and creatine kinase myocardial band, alanine aminotransferase, WBC count, neutrophils, neutrophil to lymphocyte ratio, total bilirubin, aspartate aminotransferase, lymphocytes, uric acid, lower SBP, DBP, Troponin I, red blood cell count, and ejection fraction and clinical presentation such as, palpitations, sweating, giddiness, loss of consciousness, higher Killip class, and diagnosis of inferior wall myocardial infarction. Conclusions: Higher WMR values on admission (≥1059) are associated with worse short-term outcomes in patients with ACS and independently predict short-term MACE.